RESERVOIR CHARACTERIZATION AND VOLUMETRIC ESTIMATION FS 2 â FS 5 INTERVAL, BEKASAP FORMATION, ZAPIN FIELD CENTRAL SUMATRA BASIN, RIAU, INDONESIA - Pratama, Ridho
Zapin Field is one of Central Sumatra Basin’s oil and gas fields which is part of Rokan Block, Riau. This field is currently considered as a development field within coverage area approximately 12 km2. The objectives of this study is to characterize the reservoir properties including to determine depositional enviroment of Bekasap Formation (interval FS 2 – FS 3) as well as the distribution of its facies associations, to do formation evaluation and know the distribution of reservoirs petrophysical properties, and to do subsurface mapping for resevoir geometry. Volumetric estimation is calculated in order to know the volume of original oil in place (OOIP). The data that have been involved for this study are core, biostratigraphy reports, 3D seismic and electric log from 30 wells from the research field. Core analysis presents that target intervals are consist of eight sandstone lithofacies which are Srh, Swb, Shd, Shp, Sm, Sh, Srp, and Spb, and also two siltstone-claystone lithofacies which are Flb and Fm. Based on biostratigraphy analysis, core analysis, ichnofossil and electrofacies interpretation, the depositional environment is tide dominated esturine in the age of Early Miocene; facies associations consists of Estuarine Channel, Intertidal Sand Bars, and Tidal Sand Flats, with reservoir geometry maps of channel presents a NE-SW general trend of sedimentation. Petrophysical properties in such effective porosity, permeability, effective water saturation are controlled by facies trend within NE-SW direction. Results of volumetric estimation shows the volume of Bekasap 1 as 6.187 MMBO, Bekasap 2 as 0.872 MMBO, and Bekasap 3 as 12.882 MMBO.